Boosting fire safety and mechanical performance of thermoplastic polyurethane by the face-to-face two-dimensional phosphorene/MXene architecture. (1st December 2022) - Luo, Yong; Xie, Yuhui; Geng, Wei; Chu, Junhan; Wu, Hua; Xie, Delong; Sheng, Xinxin; Mei, Yi
Highlights: A black phosphorus-MXene@polydopamine nanohybrid was synthesized. The TPU/BP-MXene@PDA nanocomposite simultaneously showed reinforcing and toughening effects towards TPU. The TPU/BP-MXene@PDA nanocomposite could be achieved excellent thermal stability, mechanical properties and flame retardancy. A synergistic flame-retardant mechanism between black phosphorus and MXene in the TPU were discussed and clarified. Abstract: Black phosphorus (BP), as one of the most promising fillers for flame retarding polymer, has been seriously limited in practical application, due to the agglomeration and poor structural stability challenges. Here, the BP was modified by MXene and polydopamine (PDA) via ultrasonication and dopamine modification strategy to improve the structural stability and dispersibility in the matrix. Then, the obtained (BP-MXene@PDA) nanohybrid was employed to promote the mechanical performance, thermal stability, and flame retardancy of thermoplastic polyurethane elastomer (TPU). The resultant TPU composite containing 2 wt.% of BP1-MXene2@PDA showed a 19.2% improvement in the tensile strength and a 13.8% increase in the elongation at break compared to those of the pure TPU. The thermogravimetric analysis suggested that BP-MXene@PDA clearly enhances the thermal stability of TPU composites. Furthermore, the introduction of the BP-MXene@PDA nanohybrids could considerably improve the flame retardancy of TPU composite, i.e., 64.2% and 27.3% decrease in peak heat release rate and total heat release, respectively. The flame-retardant mechanisms of TPU/BP-MXene@PDA in the gas phase and condensed phase were investigated systematically. This work provides a novel strategy to simultaneously enhance the fire safety and mechanical properties of TPU, thus expanding its industrial applications.